Psychiatric trainees as second victims after exposure to patient suicide: a French qualitative study - Durif-Bruckert, Christine; Cuvillier, Bruno; Vieux, Maxime; Chalancon, Benoit; Villeval, Philippe; Leaune, Edouard (Frontiers in Psychiatry, 2023)
Background: The exposure to patient suicide (PS) has been identified as one of the most frequent and troubling professional experience for psychiatric trainees. Further studies are needed to better understand how residents cope with these experiences and the association between perceived support and the impacts of PS.Method: In this qualitative study, we aimed to assess the impact of exposure to PS during psychiatric residency on trainees' professional career and practical experience. A total of 19 French psychiatric residents participated in 4 focus-groups performed between November 2017 and May 2019.Results: A total of 4 thematic clusters were identified through a five-step content analysis, namely: a) reactions to the exposure; b) coping strategies; c) professional impact; and d) prevention and postvention proposals. All participants described the critical impact of the support provided after PS, especially by their senior staff. Those who felt supported by their superior reported less negative impact, both in emotional and professional dimensions. Participants also shared proposals to improve the prevention and postvention issues related to the exposure to PS.We performed the first qualitative study based on focus groups on the impact of PS on psychiatric residents, which allowed for an in-depth understanding of the participants' lived experiences of the exposure to PS. The narratives inform the need and means to implement prevention and postvention strategies designed to buffer the negative impact of the exposure to PS in psychiatric trainees.